2021
DOI: 10.3390/antibiotics10111401
|View full text |Cite
|
Sign up to set email alerts
|

In Silico and In Vitro Evaluation of the Antimicrobial Potential of Bacillus cereus Isolated from Apis dorsata Gut against Neisseria gonorrhoeae

Abstract: Antimicrobial resistance is a major public health and development concern on a global scale. The increasing resistance of the pathogenic bacteria Neisseria gonorrhoeae to antibiotics necessitates efforts to identify potential alternative antibiotics from nature, including insects, which are already recognized as a source of natural antibiotics by the scientific community. This study aimed to determine the potential of components of gut-associated bacteria isolated from Apis dorsata, an Asian giant honeybee, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 115 publications
(120 reference statements)
0
10
0
Order By: Relevance
“…Besides, the reduced dopamine levels in our study, after exposure to FNE, may primarily be attributed to the loss of the biosynthesis enzyme TH. Previous research also revealed an interaction between FNE and DAT, a member of the Na + /Cl − -dependent transporter family and a key regulator of cytosolic dopamine concentration through molecular docking ( Niode et al, 2021 ). This interaction might have contributed to the decline in dopamine levels in FNE-exposed rats, potentially leading to increased damage to dopamine neurons ( Khoshbouei et al, 2003 ; Yoon et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the reduced dopamine levels in our study, after exposure to FNE, may primarily be attributed to the loss of the biosynthesis enzyme TH. Previous research also revealed an interaction between FNE and DAT, a member of the Na + /Cl − -dependent transporter family and a key regulator of cytosolic dopamine concentration through molecular docking ( Niode et al, 2021 ). This interaction might have contributed to the decline in dopamine levels in FNE-exposed rats, potentially leading to increased damage to dopamine neurons ( Khoshbouei et al, 2003 ; Yoon et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, lipophilicity and various toxicity parameters (LD 50 , hepatotoxicity, and AMES toxicity) were anticipated by using pkCSM online server [ 46 ]. Compounds used as input were obtained from the PubChem database using their canonical SMILES [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…The EE solution was diluted with distilled water until its concentration was 10 -2 and 10 -4 times its initial value (10 0 ). Then the solution was heated in the thermoblock at 80 °C for one hour and centrifuged for 1 min at 6000 rpm [24]. The supernatant, as well as the positive and negative controls, were added to the well in quantities up to 50 μl.…”
Section: Evaluation Of Inhibition Capacity Of Ee Solution Againstmentioning
confidence: 99%